STUDY OF PATTERN OF INFECTION IN BURN WOUNDS IN A TERTIARY CARE HOSPITAL IN UJJAIN CITY - VISHAL DUBEY; SANJEEW KUMAR CHOUDHARY (International Journal of Pharma and Bio Sciences, 2012)
Infection is the commonest and the most serious problem in patients who survive the shock phase of major thermal injury. It is the most important cause of mortality and morbidity in burn patients. The present paper attempts to study the bacterial profile of burn wounds. One hundred and fifty patients admitted with burn injury were studied. Patients received routine resuscitation and local wound care. A surface swab specimen was collected for bacterial culture and sensitivity test. Total 510 swab cultures were obtained. Among 510 positive swab cultures obtained, Pseudomonas (48.62%) was the most frequent single organism isolated and gram negative organisms (76.87%) outnumbered the gram positive ones (23.13%). This study proved that Pseudomonas was the commonest single organism isolated, and gram negative organisms exceeded the gram positive ones.